EFFECT OF PENICILLIN -CIPROFLOXACIN COMBINATION ON SEMEN CHARACTERISTIC AND BACTERIAL CONTAMINANTS OF DILUTED BULL SEMEN - ALI, N.A. MOHAMMED; AL-BADRY, K. I.; AL-HISSEN, S. F.; AL-KAFAGI, B. A.; AL-HISSEN, S. F. (The Iraqi Journal of Veterinary Medicine, 2021)
Effect of penicillin- ciprofloxacin combinations on some semen characteristics and bacterial contaminants of diluted bull semen was determined and compared with those of penicillin- streptomycin combinations. Sperm motility, percentage of dead and abnormal spermatozoa and survival index did not differ significantly for penicillin (1000 IU) and ciprofloxacin (125, 250, 500, 1000 ug) combinations per milliliter of diluted bull semen from those of penicillin (1000 I.U) and streptomycin (500 ug) combination / ml. Each penicillin ciprofloxacin combination effectively controlled bacterial growth. However penicillin streptomycin combination did not effectively control the growth. Accordingly, the combination of penicillin- ciprofloxacin seems to be a satisfactory substituent for penicillin- streptomycin combination for controlling bacterial contaminants in diluted bull semen without impairing semen characteristics.